Rapid hybridization kinetics of DNA attached to submicron latex particles. - Wolf, S F (1987)
We describe a novel method for attaching any DNA molecule to submicron latex beads and characterize the hybridization kinetic properties of these bead-DNA conjugates. The conjugates hybridize to DNA in solution with rates comparable to homogeneous hybridization reactions, are compatible with common hybridization conditions and are conveniently manipulated. They should thus serve as useful reagents for the fractionation and characterization of DNA and RNA.